Effects of soil properties on hysteresis of soil - Effendi, Arifin (2010)
The hysteresis of soil is one of the important phenomena that needs to be understood for better understanding of soil behaviour. The objective of this study is to understand the impact of different soil properties on the hysteresis of soil and vice versa. By preparing different specimens under cycles of drying and wetting, the soil-water characteristic curve can be obtained and analyzed to find correlation between soil-water characteristic curve (SWCC) and soil properties and SWCC equation. A total of 8 different specimens were studied. The study showed that soils with higher initial saturated water content tend to have steeper SWCC slope while soils with higher density tend to have higher air-entry value, higher value of parameter a and lower value of parameter n. For a coarser soil, air-entry value tends to be higher and the parameter m value tends to become lower. Two hysteresis indices are also proposed in this study for quantifying the total hysteresis of a soil based on the basic properties and a, n, m values from Fredlund and Xing equation (1994). By understanding the effect of basic soil properties, a, n, m values and hysteresis assists engineers to obtain a more accurate estimation of SWCC.